Associations of hypertension and/or diabetes and the risk of dementia according to participation in social activities from an age-specific community-based cohort study (the NISSIN Project) - Rika Taniguchi; Shigekazu Ukawa; Wenjing Zhao; Satoe Okabayashi; Takashi Kimura; Yifan Shan; Masahiko Ando; Kenji Wakai; Kazuyo Tsushita; Takashi Kawamura; Akiko Tamakoshi (Archives of Gerontology and Geriatrics Plus)
Aim: This study investigated the association between participation in social activities and incident dementia among physically and socially independent older adults with or without diseases (hypertension and/or diabetes mellitus) in a Japanese age-specific cohort (the NISSIN Project). Methods: We conducted a prospective cohort study of 1,856 Japanese individuals (953 men and 903 women) aged 64/65 years. Information on medical status, demographics, and lifestyle characteristics was collected using a baseline questionnaire and health checkup (2000–2005). Incident dementia were confirmed among these received long-term care certifications using the nationally standardized dementia scale proposed by the Ministry of Health, Labor, and Welfare. A competing risk model was used to calculate hazard ratios (HRs) and 95 % confidence intervals (CIs) for dementia incidence. We treated the censored cases of death as competing events. Results: During a median of 16.0 years of follow-up, incident dementia occurred in 332 participants. The presence of diseases and nonparticipation in social activities were associated with a significantly higher risk of incident dementia (HR 1.65; 95 % CI 1.21–2.26) after adjusting for potential confounders compared with participants without diseases and those who participated in social activities. Conclusions: In this age-specific cohort study, participants with diseases and those who did not participate in social activities were more likely to have incident dementia than those without diseases and those who participated in social activities. For older people with hypertension and/or diabetes mellitus, engaging in social activities could be a beneficial strategy for reducing the risk of developing dementia.